Perovskite cells, methods of making and use thereof

CN122995391APending Publication Date: 2026-10-27HUNAN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611361079.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

尽管取得了这一进展,ZnO基器件的性能仍受到若干固有缺陷的限制

Benefits of technology

本发明提供了一种CsPbI2Br钙钛矿电池。该电池在SnO2ETL与CsPbI2Br薄膜之间插入Al掺杂ZnO(AZO)中间层。该中间层可在不对钙钛矿吸收层施加任何钝化或掺杂处理的情况下,可使CsPbI2Br电池的功率转换效率达到16.52%。AZO是一种宽带隙透明导电氧化物,已广泛用于光电器件;但现有技术并没有将其作为SnO2与全无机钙钛矿之间界面修饰层。AZO中间层不仅充当桥梁,在SnO2/AZO/CsPbI2Br钙钛矿薄膜三层之间建立级联能级对齐、最大限度地降低电子抽取的能量势垒,还能促进高质量CsPbI2Br薄膜的生长,使其结晶性提高、界面陷阱态密度降低。更具体的,本发明提供的CsPbI2Br钙钛矿电池的器件结构为ITO/SnO2/AZO/CsPbI2Br/PTAA/MoO3/Ag。该结构的器件高达16.52%的PCE已是未经钙钛矿后处理的全无机PSC中的最高值之一。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995391A_ABST
    Figure CN122995391A_ABST
Patent Text Reader

Abstract

The application provides a perovskite battery, which comprises a transparent electrode, wherein the transparent electrode is loaded with a SnO2 film on the surface; the SnO2 film is loaded with an aluminum-doped zinc oxide film on the surface; the aluminum-doped zinc oxide film is loaded with a CsPbI2Br film on the surface; the CsPbI2Br film is loaded with a composite hole transport layer on the surface; and the composite hole transport layer is loaded with a metal electrode on the surface. The application also provides a preparation method of the perovskite battery and application of the perovskite battery in the field of power generation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of perovskite solar cells, specifically to a CsPbI2Br perovskite solar cell, its preparation method, and its applications. Background Technology

[0002] All-inorganic cesium lead halide perovskites (CsPbX3, X = I, Br, Cl) are attractive photovoltaic materials due to their superior thermal stability compared to organic-inorganic hybrid perovskites, which typically fail under external thermal stress due to the migration and decomposition of volatile organic cations. Within the CsPbX3 family, CsPbI2Br achieves a good balance between a bandgap of approximately 1.91 eV and phase stability, making it a strong candidate for fabricating wide-bandgap single-junction solar cells and top cells in tandem structures. Recent advances have increased the power conversion efficiency (PCE) of CsPbI2Br perovskite solar cells (PSCs) to over 19%. However, energy level mismatch at the electron transport layer (ETL) / perovskite interface adversely affects charge extraction, thus limiting the open-circuit voltage (Voc) below the Shockley-Queisser limit. To address this issue, two main strategies have been proposed. The first is bulk doping, specifically Li... + K + 、Rb + Ca 2+ Mn 2+ In 3+ or Cl - One approach involves introducing foreign ions into the perovskite lattice to modulate its crystal structure and suppress ion migration. Another approach is surface passivation, typically achieved by saturating uncoordinated surface defects using organic ammonium salts or Lewis bases. While these methods have proven effective, they inevitably add extra processing steps, raise concerns about long-term chemical compatibility, and in some cases, compromise the intrinsic photoelectric properties of perovskite. Furthermore, the interaction between dopants or passivators and the perovskite matrix remains poorly understood, often resulting in poor batch-to-batch reproducibility. Therefore, there is an urgent need for an alternative route that completely bypasses perovskite modification while still effectively eliminating interfacial recombination loss channels.

[0003] ZnO has been widely used in organic solar cells due to its much higher electron mobility than TiOX and SnO2, as well as its excellent doping potential. However, because it reacts with organic cations (MA... + or FA +The deprotonation reaction of ZnO significantly limits its application in hybrid perovskite solar cells. In contrast, all-inorganic PSCs do not suffer from this problem. Nevertheless, the potential of the ZnO family in all-inorganic perovskites has been largely overlooked. Yan et al. demonstrated that the SnO2 / ZnO double electron transport layer (ETL) can effectively modulate interface energy level alignment. The high conduction band bottom of ZnO facilitates favorable cascade energy level alignment between the perovskite and the SnO2 / ZnOETL, thereby enhancing electron extraction and suppressing interfacial recombination. Based on this strategy, an all-inorganic CsPbI2Br solar cell achieved an open-circuit voltage of 1.23 V and a power conversion efficiency of 14.6%. Despite this progress, the performance of ZnO-based devices remains limited by several inherent defects. Solution-prepared ZnO films typically suffer from inhomogeneous morphology and high surface roughness, leading to poor interfacial contact and increased defect density at the ETL / perovskite interface. Meanwhile, the intrinsic high concentration of oxygen vacancies in ZnO introduces deep-level trap states, promoting nonradiative recombination and limiting achievable VOCs. Furthermore, the insufficient conduction band bottom of ZnO prevents it from establishing an energy-friendly cascade alignment with the perovskite layer, resulting in insufficient electron extraction driving force and thus limiting charge extraction efficiency at the ETL / perovskite interface. Summary of the Invention

[0004] The first objective of this invention is to provide a perovskite solar cell with high power conversion efficiency.

[0005] A second objective of the present invention is to provide a method for preparing the perovskite solar cell.

[0006] A third object of the present invention is to provide the application of the perovskite solar cell.

[0007] This invention is achieved through the following technical solution: A perovskite solar cell includes a transparent electrode, the surface of which is loaded with a SnO2 thin film. The surface of the SnO2 film is loaded with an aluminum-doped zinc oxide film; The surface of the aluminum-doped zinc oxide film is loaded with a CsPbI2Br film. The surface of the CsPbI2Br thin film is loaded with a composite hole transport layer. The surface of the composite hole transport layer is loaded with metal electrodes.

[0008] The transparent electrode comprises ITO glass; The aluminum doping content in the aluminum-doped zinc oxide film is 1-5 at%; The composite hole transport layer comprises a PTAA film and a MoO3 film; The metal electrode may be gold or silver.

[0009] The method for preparing the perovskite solar cell includes the following steps: SnO2 colloidal solution was first spin-coated onto the surface of a transparent electrode and then subjected to a first annealing to load a SnO2 thin film on the surface of the transparent electrode. A ZnO colloidal solution containing aluminum ions is spin-coated onto the surface of a SnO2 film and then subjected to a second annealing to load an aluminum-doped zinc oxide film onto the surface of the SnO2 film. A CsPbI2Br precursor solution was spin-coated onto the surface of an aluminum-doped zinc oxide film for the third time, followed by a third annealing, in order to load a CsPbI2Br film onto the surface of the aluminum-doped zinc oxide film. A composite hole transport layer is loaded onto the surface of a CsPbI2Br thin film; By loading a metal electrode onto the surface of the composite hole transport layer, it is obtained.

[0010] The method for preparing the perovskite solar cell further includes a step of hydrophilizing the transparent electrode; The hydrophilization includes the step of treating the transparent electrode with ultraviolet light in an ozone atmosphere; The ultraviolet treatment time is 16 minutes.

[0011] The method for preparing the SnO2 colloidal solution includes the step of diluting a raw SnO2 solution with a concentration of 11-13 wt% with water at a volume ratio of 1:3.5-4.5; The temperature of the first annealing is 140-160℃, and the time is 25-35 min; The first spin coating speed is 4500-5500 rpm.

[0012] The method for preparing the ZnO colloidal solution containing aluminum ions includes the following steps: Zinc salt was dissolved in alcohol, then monoethanolamine was added, and the solution was diluted with alcohol to obtain a ZnO colloidal solution; aluminum nitrate nonahydrate was added to the ZnO colloidal solution. The zinc salt includes zinc acetate dihydrate; The weight-to-volume ratio of zinc acetate dihydrate to alcohol is 16-18 g: 100 mL; The volume ratio of the alcohol to monoethanolamine is 100:7-8; The alcohol includes ethanol; The solid content of the ZnO colloidal solution is 2-3 wt%. The amount of aluminum nitrate nonahydrate added is 0.09-0.48 g of aluminum nitrate nonahydrate per 100 mL of ZnO colloidal solution; The second annealing temperature is 140-160℃, and the time is 25-35 min; The second spin coating speed is 4500-5500 rpm.

[0013] The preparation method of the CsPbI2Br precursor solution includes dissolving CsI, PbI2 and PbBr2 in dimethyl sulfoxide in a molar ratio of 2:1:1 and stirring at 65°C for 3 hours. The concentration of the CsPbI2Br precursor solution was 1 mol / L; The third spin coating includes the following steps: First spin-coat at 1000 rpm for 10 seconds, then spin-coat at 3000 rpm for 40 seconds, and then heat-treat at 100°C within 15 seconds before the end of the third spin-coating. The third annealing includes the following steps: Anneal at 50℃ for 30 seconds, then anneal at 200℃ for 10 minutes; The method for preparing the composite hole transport layer includes the following steps: A 10 mg / mL PTAA chlorobenzene solution was spin-coated onto the surface of a CsPbI2Br film at 4000 rpm for 30 s, followed by annealing at 100 °C for 15 min to obtain a PTAA film. A 6 nm thick MoO3 film was loaded onto the surface of a PTAA film using a thermal evaporation method under vacuum.

[0014] The method for preparing the metal electrode includes the following steps: A 100 nm thick Ag or Au film was loaded onto the surface of a MoO3 film under vacuum using a thermal evaporation method.

[0015] The perovskite battery described above is used for power generation.

[0016] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a CsPbI2Br perovskite solar cell. The cell incorporates an Al-doped ZnO (AZO) interlayer between a SnO2 ETL and a CsPbI2Br thin film. This interlayer enables the CsPbI2Br cell to achieve a power conversion efficiency of 16.52% without any passivation or doping treatment of the perovskite absorber layer. AZO is a wide-bandgap transparent conductive oxide widely used in optoelectronic devices; however, it has not been used as an interface modification layer between SnO2 and the all-inorganic perovskite in existing technologies. The AZO interlayer not only acts as a bridge, establishing cascaded energy level alignment among the three SnO2 / AZO / CsPbI2Br perovskite thin film layers and minimizing the energy barrier for electron extraction, but also promotes the growth of high-quality CsPbI2Br thin films, improving their crystallinity and reducing the density of interface trap states. More specifically, the CsPbI2Br perovskite solar cell device structure provided by this invention is ITO / SnO2 / AZO / CsPbI2Br / PTAA / MoO3 / Ag. This structure achieves a PCE of up to 16.52%, which is among the highest values ​​for all-inorganic PSCs without perovskite post-treatment.

[0017] The CsPbI2Br perovskite solar cell provided by this invention improves the performance of all-inorganic CsPbI2Br perovskite solar cells by introducing an AZO interlayer between the SnO2 electron transport layer and the perovskite absorber layer. The AZO interlayer facilitates favorable cascaded energy level alignment between the SnO2 / AZO / perovskite layers, lowers the electron extraction barrier, and simultaneously blocks hole backflow. Furthermore, the introduction of Al atoms suppresses oxygen vacancy formation, thereby promoting better perovskite crystallinity and faster charge extraction. The CsPbI2Br perovskite solar cell provided by this invention exhibits suppressed dark current, lower trap density, weaker nonradiative recombination, and a smaller hysteresis exponent.

[0018] The CsPbI2Br perovskite solar cell provided by this invention retains 80% of its initial efficiency after 662 hours of continuous illumination in nitrogen, while ZnO-based devices only achieve 312 hours. More importantly, the efficient charge extraction and hole backflow prevention capabilities of SnO2 / AZO can alleviate Ag electrode degradation and corrosion. This is clearly demonstrated by the suppression of interfacial void formation and electrode fragmentation in AZO-based devices. Attached Figure Description

[0019] Figure 1 a shows a surface SEM image of the CsPbI2Br perovskite film deposited on an ITO / SnO2 / ZnO substrate in the CsPbI2Br perovskite solar cell prepared in Comparative Example 1. Figure 1b shows a surface SEM image of the CsPbI2Br perovskite film deposited on an ITO / SnO2 / AZO substrate in the CsPbI2Br perovskite solar cell prepared in Example 1; Figure 1 c shows a cross-sectional SEM image of ITO / SnO2 / ZnO / CsPbI2Br in the CsPbI2Br perovskite solar cell prepared in Comparative Example 1. Figure 1 Figure d shows a cross-sectional SEM image of ITO / SnO2 / AZO / CsPbI2Br in the CsPbI2Br perovskite solar cell prepared in Example 1; Figure 1 e shows a SEM image of the ZnO thin film on ITO / SnO2 in the CsPbI2Br perovskite solar cell prepared in Comparative Example 1. Figure 1 f shows a SEM image of the AZO thin film in the CsPbI2Br perovskite solar cell prepared in Example 1; Figure 1 g shows the AFM two-dimensional height map of the SnO2 / ZnO double electron transport layer in the CsPbI2Br perovskite solar cell prepared in Comparative Example 1; Figure 1 h shows an AFM two-dimensional height map of the SnO2 / AZO double electron transport layer in the CsPbI2Br perovskite solar cell prepared in Example 1.

[0020] Figure 2 a shows the O 1s spectra (containing lattice oxygen) of the ZnO film in the CsPbI2Br perovskite solar cell prepared in Comparative Example 1 and the AZO film in the CsPbI2Br perovskite solar cell prepared in Example 1. 2- (and oxygen vacancy (OV) unconvolution integral peaks). Figure 2 b shows the Al 2p spectra of the ZnO film in the CsPbI2Br perovskite solar cell prepared in Comparative Example 1 and the AZO film in the CsPbI2Br perovskite solar cell prepared in Example 1. Figure 2 c shows the Zn 2p spectra of the ZnO film in the CsPbI2Br perovskite solar cell prepared in Comparative Example 1 and the AZO film in the CsPbI2Br perovskite solar cell prepared in Example 1. Figure 2Figure d shows the XRD pattern of the CsPbI2Br perovskite film deposited on the SnO2 / ZnO substrate in the CsPbI2Br perovskite solar cell prepared in Comparative Example 1 and the XRD pattern of the CsPbI2Br perovskite film deposited on the SnO2 / AZO substrate in the CsPbI2Br perovskite solar cell prepared in Example 1. Figure 2 e shows the UPS spectra of the ZnO film in the CsPbI2Br perovskite solar cell prepared in Comparative Example 1 and the AZO film in the CsPbI2Br perovskite solar cell prepared in Example 1. Figure 2 f shows the corresponding band diagram derived from UPS measurements.

[0021] Figure 3 a shows the original UPS spectrum of the ZnO thin film in the CsPbI2Br perovskite solar cell prepared in Comparative Example 1; Figure 3 b shows the original UPS spectrum of the AZO thin film in the CsPbI2Br perovskite solar cell prepared in Example 1; Figure 3 c shows the optical band gaps of ZnO in the CsPbI2Br perovskite solar cell prepared in Comparative Example 1 and AZO in the CsPbI2Br perovskite solar cell prepared in Example 1, determined by UV-Vis absorption spectroscopy, wherein the two spectra almost overlap.

[0022] Figure 4 a shows a PL image of the CsPbI2Br perovskite thin film deposited on an ITO / SnO2 / ZnO substrate prepared in Comparative Example 1. Figure 4 b shows a PL image of the CsPbI2Br perovskite thin film deposited on an ITO / SnO2 / AZO substrate prepared in Example 1; Figure 4 c shows a TRPL image of the CsPbI2Br perovskite film deposited on an ITO / SnO2 / ZnO substrate prepared in Comparative Example 1. Figure 4 d shows a TRPL image of the CsPbI2Br perovskite thin film deposited on an ITO / SnO2 / AZO substrate prepared in Example 1; Figure 4 Figure e shows the excitation intensity-dependent TRPL decay curves of the CsPbI2Br perovskite thin film deposited on an ITO / SnO2 / ZnO substrate prepared in Comparative Example 1; the inset shows the variation of the average carrier lifetime (τave) with laser power obtained by the double exponential fitting of TRPL decay.

[0023] Figure 4 Figure f shows the excitation intensity-dependent TRPL decay curve of the CsPbI2Br perovskite film deposited on an ITO / SnO2 / AZO substrate prepared in Example 1; the inset shows the variation of the average carrier lifetime (τave) with laser power obtained by the double exponential fitting of TRPL decay.

[0024] Figure 4 g shows the corresponding steady-state PL spectra of the device ITO / SnO2 / ZnO / CsPbI2Br / PTAA / MoO3 / Ag prepared in Comparative Example 1 and the corresponding steady-state PL spectra of the device ITO / SnO2 / AZO / CsPbI2Br / PTAA / MoO3 / Ag prepared in Example 1.

[0025] Figure 4 h shows the transient photocurrent (TPC) decay curves of the device ITO / SnO2 / ZnO / CsPbI2Br / PTAA / MoO3 / Ag prepared in Comparative Example 1 and the transient photocurrent (TPC) decay curves of the device ITO / SnO2 / AZO / CsPbI2Br / PTAA / MoO3 / Ag prepared in Example 1.

[0026] Figure 5 a shows the J-V curves of the ZnO-based perovskite solar cell prepared in Comparative Example 1 and the AZO-based perovskite solar cell prepared in Example 1. Figure 5 b shows the EQE spectrum and integrated current density of the ZnO-based perovskite solar cell prepared in Comparative Example 1 and the AZO-based perovskite solar cell prepared in Example 1. Figure 5 c shows the stable power output and steady-state current density at the maximum power point of the perovskite solar cell based on ZnO prepared in Comparative Example 1 and the perovskite solar cell based on AZO prepared in Example 1. Figure 5 Figure d shows the VOC variation with light intensity and the fitting slope (nk) of the perovskite solar cell based on ZnO prepared in Comparative Example 1 and the perovskite solar cell based on AZO prepared in Example 1. B T / q); Figure 5 e shows the dark current-voltage curves of the ZnO-based perovskite solar cell prepared in Comparative Example 1 and the AZO-based perovskite solar cell prepared in Example 1. Figure 5 f shows the forward and reverse scan J-V curves of the AZO-based perovskite solar cell prepared in Example 1.

[0027] Figure 6 Different Al were shown3+ J–V curves of CsPbI2Br perovskite devices in ZnO electron transport layers with varying doping concentrations; Figure 7 The forward and reverse scan J-V curves of the ZnO-based device, the ITO / SnO2 / ZnO / CsPbI2Br / PTAA / MoO3 / Ag device prepared in Comparative Example 1, are shown. Figure 8 a shows the PCE statistical distribution of the ITO / SnO2 / ZnO / CsPbI2Br / PTAA / MoO3 / Ag devices prepared in Comparative Example 1 and the ITO / SnO2 / AZO / CsPbI2Br / PTAA / MoO3 / Ag devices prepared in Example 1 (25 devices in each group). Figure 8 b shows the UV-Vis absorption spectra of the ITO / SnO2 / ZnO / CsPbI2Br / PTAA / MoO3 / Ag device prepared in Comparative Example 1 and the ITO / SnO2 / AZO / CsPbI2Br / PTAA / MoO3 / Ag device prepared in Example 1. Figure 8 c shows the Nyquist plots of EIS measurements and the corresponding equivalent circuit models of the ITO / SnO2 / ZnO / CsPbI2Br / PTAA / MoO3 / Ag device prepared in Comparative Example 1 and the ITO / SnO2 / AZO / CsPbI2Br / PTAA / MoO3 / Ag device prepared in Example 1. Figure 8 Figure d shows the SCLC curves and extracted trap filling limit voltages (V) of the ITO / SnO2 / ZnO / CsPbI2Br / PTAA / MoO3 / Ag device prepared in Comparative Example 1 and the ITO / SnO2 / AZO / CsPbI2Br / PTAA / MoO3 / Ag device prepared in Example 1. TFL ); Figure 8 e shows the trap density of states (tDOS) of the ITO / SnO2 / ZnO / CsPbI2Br / PTAA / MoO3 / Ag device prepared in Comparative Example 1 and the ITO / SnO2 / AZO / CsPbI2Br / PTAA / MoO3 / Ag device prepared in Example 1, derived from thermal conductivity nanospectroscopy. Figure 8 f shows the J-V curves of the ITO / SnO2 / ZnO / CsPbI2Br / PTAA / MoO3 / Ag device prepared in Comparative Example 1 and the ITO / SnO2 / AZO / CsPbI2Br / PTAA / MoO3 / Ag device prepared in Example 1.

[0028] Figure 9 The normalized PCE decay curves of the unencapsulated CsPbI2Br perovskite solar cell without antireflection coating prepared in Comparative Example 1 under continuous AM 1.5G illumination in a nitrogen atmosphere and the normalized PCE decay curves of the unencapsulated CsPbI2Br perovskite solar cell without antireflection coating prepared in Example 1 under continuous AM 1.5G illumination in a nitrogen atmosphere are shown. Figure 10 Image a shows a top-view SEM image of the device ITO / SnO2 / AZO / CsPbI2Br / PTAA / MoO3 / Ag prepared in Example 1 after continuous AM 1.5G illumination for 700 h in a nitrogen atmosphere.

[0029] Figure 10 b shows a top-view SEM image of the device ITO / SnO2 / ZnO / CsPbI2Br / PTAA / MoO3 / Ag prepared in Comparative Example 1 after continuous AM 1.5G illumination for 700 h in a nitrogen atmosphere.

[0030] Figure 10 c shows a cross-sectional SEM image of the device ITO / SnO2 / AZO / CsPbI2Br / PTAA / MoO3 / Ag prepared in Example 1 after continuous AM 1.5G illumination for 700 h in a nitrogen atmosphere.

[0031] Figure 10 Figure d shows a cross-sectional SEM image of the device ITO / SnO2 / ZnO / CsPbI2Br / PTAA / MoO3 / Ag prepared in Comparative Example 1 after continuous AM 1.5G illumination for 700 h in a nitrogen atmosphere. Detailed Implementation

[0032] The materials involved in the specific embodiments of the present invention are as follows: Cesium iodide (CsI, 99.999%), lead iodide (PbI2, 99.999%), lead bromide (PbBr2, 99.99%), poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine] (PTAA, Mw 6,000–15,000) and SnO2 colloidal solution (12 wt%, aqueous solution) were purchased from Xi'an Sunlight Energy Technology Co., Ltd.

[0033] Chlorobenzene (CB, 99.8%), dimethyl sulfoxide (DMSO, 99.7%), aluminum nitrate nonahydrate (Al(NO3)3·9H2O, 99.997%), and zinc acetate dihydrate (C4H6O4Zn·2H2O, ≥99%) were purchased from Sigma.

[0034] Ethanol (C2H5OH, 99.99%) and 2-aminoethanol (C2H7NO, ≥99.5%) were purchased from Adamas.

[0035] Silver (Ag, 99.99%) and MoO3 (99.99%) were purchased from Zhongnuo Advanced Materials (Beijing) Technology Co., Ltd.

[0036] The characteristics involved in specific embodiments of the present invention are as follows: X-ray diffraction (XRD) was performed using a Bruker D8 ADVANCE diffractometer with Cu Kα radiation (λ = 1.5418 Å).

[0037] The surface morphology and cross-sectional microstructure of the perovskite thin film were observed using a Navi innovation and Helios NanoLab G3 UC dual-beam scanning electron microscope (SEM).

[0038] The ultraviolet-visible absorption spectra were recorded on a Thermo-Scientific Evolution 201 spectrophotometer, with a wavelength range of 300–900 nm.

[0039] Steady-state photoluminescence (PL) spectra were acquired using an iHR 320 spectrometer (LDHD-C-405 laser, PicoQuant) with an excitation wavelength of 337 nm.

[0040] The device's current density–voltage (J–V) characteristics were measured under AM 1.5G illumination (100 mW•cm²) provided by a xenon lamp solar simulator (Newport Oriel 66902). -2 Under these conditions, measurements were taken using a Keithley 2450 source meter.

[0041] The external quantum efficiency (EQE) spectrum was recorded by the EQE measurement system (Enli Technology).

[0042] For a single-electron device, the J-V curves are recorded in the dark using a Keithley 2450 source table.

[0043] Transient photocurrent (TPC) measurements were performed using a pulsed nitrogen laser (NL100, 337nm) in conjunction with a digital oscilloscope (Tektronix MDO 3102).

[0044] The capacitance-voltage (C–V) and capacitance-frequency (C–f) characteristics were measured using an electrochemical workstation (Ivium Vertex, Netherlands), and the trap density of states (tDOS) was extracted by thermal conductance spectroscopy (TAS) analysis.

[0045] Time-resolved photoluminescence (TRPL) measurements were performed using a 405 nm pulsed laser as the excitation source with a repetition frequency of 40 MHz. The PL intensity imaging and attenuation curves of the perovskite thin film were acquired by a time-correlated single-photon counting (TCSPC) system (HydraHarp 400, PicoQuant).

[0046] Example 1 The ITO glass substrate was ultrasonically cleaned for 20 minutes each in glass cleaning agent, deionized water, acetone and ethanol, and then subjected to UV-ozone treatment for 16 minutes before film deposition to make the surface hydrophilic.

[0047] A commercial SnO2 colloidal solution (12wt%) was diluted with ultrapure water at a volume ratio of 1:4, spin-coated onto an ITO substrate at 5000 rpm for 30 s, and then annealed at 150 °C for 30 min.

[0048] Dissolve 17.56 g of zinc acetate dihydrate in about 100 mL of anhydrous ethanol and stir continuously until completely dissolved. Then add 7.20 mL of monoethanolamine dropwise and dilute with anhydrous ethanol to obtain a 2.5 wt% ZnO colloidal solution.

[0049] Add 0.28 g of aluminum nitrate nonahydrate to 100 mL of 2.5 wt% ZnO colloidal solution to achieve a nominal doping concentration of 3 at%.

[0050] The AZO colloidal solution was diluted with anhydrous ethanol (1:4) and spin-coated onto an ITO substrate covered with SnO2 at 5000 rpm for 30 s, followed by annealing at 150 °C for 30 min.

[0051] The CsPbI2Br precursor solution (concentration 1M) was prepared by dissolving CsI, PbI2 and PbBr2 in dimethyl sulfoxide (DMSO) in a molar ratio of 2:1:1 and stirring at 65°C for 3 hours.

[0052] The precursor solution was then spin-coated onto the AZO / SnO2 / ITO substrate using a two-step process: first at 1000 rpm for 10 s, then at 3000 rpm for 40 s. During the last 15 s of spin-coating, the sample was heated with a hot air gun (100 °C) at a distance of 3.5–4 cm above the substrate to induce the formation of a transitional light brown intermediate state. After spin-coating, the film was annealed sequentially at 50 °C for 30 s and then at 200 °C for 10 min.

[0053] The PTAA hole transport layer was formed by spin-coating a PTAA solution (10 mg / mL, chlorobenzene solvent) at 4000 rpm for 30 s, followed by annealing at 100 °C for 15 min.

[0054] Finally, MoO3 (6 nm) and Ag (100 nm) were thermally evaporated under vacuum, and the effective area of ​​the device was defined as 0.08 cm². 2 .

[0055] Example 2 The difference from Example 1 is that 0.09 g of aluminum nitrate nonahydrate was added to 100 mL of 2.5 wt% ZnO colloidal solution to achieve a nominal doping concentration of 1 at%.

[0056] Example 3 The difference from Example 1 is that 0.48 g of aluminum nitrate nonahydrate was added to 100 mL of 2.5 wt% ZnO colloidal solution to achieve a nominal doping concentration of 5 at%.

[0057] Comparative Example 1 The difference from Example 1 is that aluminum nitrate nonahydrate is not added.

[0058] The technical solution provided in Embodiment 1 of the present invention prepares ZnO and AZO thin films using corresponding precursor solutions via sol-gel spin coating and deposits them on an ITO substrate covered with SnO2.

[0059] like Figure 1 As shown, compared with the CsPbI2Br thin film on ZnO prepared in Comparative Example 1, the CsPbI2Br thin film prepared in Example 1 has denser grain boundaries and closer inter-grain contact.

[0060] Figure 1 The cross-sectional view shows that the interface between the perovskite layer and the AZO intermediate layer in the CsPbI2Br perovskite solar cell prepared in Example 1 is more compact. This indicates that the AZO prepared in Example 1 is more conducive to the crystallization and growth of CsPbI2Br thin film than the ZnO prepared in Comparative Example 1.

[0061] Figure 1 The surface morphology shows that the AZO film prepared in Example 1 has a more uniform coverage, while the ZnO film prepared in Comparative Example 1 shows a more obvious island-like distribution.

[0062] Figure 1 In the AFM two-dimensional surface height map, the root mean square roughness (R) q The wavelengths are 1.11 nm and 1.00 nm, respectively. As can be seen from the figure, the AZO film prepared in Example 1 has lower surface roughness and more uniform coverage, which is beneficial for forming a close contact with the upper perovskite layer.

[0063] This invention performed peak fitting on the O1s XPS spectra of the AZO thin film in the perovskite solar cell prepared in Example 1 and the O1s XPS spectra of the ZnO thin film in the perovskite solar cell prepared in Comparative Example 1. The O1s spectrum was deconvolved into two components: lattice oxygen (O2) located at 529.9 eV. 2- ) and oxygen vacancy (OV) at 531.6 eV.

[0064] like Figure 2 As shown in Figure a, the lattice oxygen content in the AZO film prepared in Example 1 is 2.1% higher than that in the ZnO film, and the oxygen vacancies are correspondingly reduced by 2.1%. The decrease in oxygen vacancy concentration indicates that the surface of the AZO film is closer to the stoichiometry and has fewer defect states, which is beneficial for suppressing nonradiative recombination at the interface and promoting efficient electron extraction at the ETL / perovskite interface.

[0065] Figure 2 b shows the Al2p spectrum of the AZO thin film prepared in Example 1. Figure 2 A distinct peak can be clearly observed at 73.9 eV in b, which is Al 3+ The characteristic peaks of ion substitution into the ZnO lattice, rather than the formation of the segregated Al2O3 phase (typically located above 74.2 eV), are observed. 3+ For Zn 2+ The successful substitution induced a charge compensation effect, thereby fundamentally suppressing the formation of oxygen vacancies; this is quantitatively consistent with the result that the OV content in the O1s spectrum decreased by 2.1%.

[0066] like Figure 2 As shown in Figure c, the Zn 2p3 / 2 binding energy of the AZO thin film prepared in Example 1 shifts from 1021.19 eV for ZnO to 1021.07 eV for AZO. This negative shift is consistent with the upward shift of the Fermi level and is a direct result of the increased carrier concentration caused by successful Al doping.

[0067] Figure 2 Figure d shows the XRD patterns of the CsPbI2Br perovskite film deposited on an ITO / SnO2 / ZnO substrate prepared in Comparative Example 1 and the XRD patterns of the CsPbI2Br perovskite film deposited on an ITO / SnO2 / AZO substrate prepared in Example 1. The diffraction peaks at 14.74° and 29.68° correspond to the (100) and (200) crystal planes of the α-phase (cubic phase) CsPbI2Br, respectively, while the peak at 10.16° belongs to the δ-phase (yellow phase). The XRD patterns indicate that the CsPbI2Br film grown on the ITO / SnO2 / AZO substrate exhibits excellent cubic phase crystallinity and does not contain the δ-phase, essentially forming a pure-phase all-inorganic perovskite film. Therefore, the AZO substrate is more conducive to the crystallization and growth of the CsPbI2Br film.

[0068] This invention performed ultraviolet photoelectron spectroscopy (UPS) analysis on the ZnO thin films prepared in Comparative Example 1 and the AZO thin films prepared in Example 1. The spectra are shown below. Figure 2 As shown in Figure e, the work function (WF) and valence band maxima (VBM) are derived from the second electron cutoff (Ecutoff) in the range of 17–19 eV and the valence band initiation (Eonset) in the range of 0–7 eV, respectively. The corresponding band structure diagram is shown in Figure e. Figure 2 f.

[0069] For detailed UV-Vis absorption spectra and UPS spectra, as well as the derived parameters, please refer to [link to relevant documentation]. Figure 3 See Table 1.

[0070] Table 1 from Figure 3 As can be seen, the Al-doped Burstein-Moss effect shifts both the conduction band bottom and valence band top of AZO upwards relative to ZnO. Simultaneously, the work function slightly increases from 3.61 eV in ZnO to 3.66 eV in AZO. The upward shift in the conduction band and the increased work function create a more favorable energy gradient between SnO2 and perovskite, which not only lowers the electron extraction barrier but also effectively blocks hole backflow, thus significantly improving interfacial charge extraction. The UPS spectrum, along with the 2.1% reduction in oxygen vacancies observed by XPS, together explain the significantly suppressed interfacial recombination and the increased Voc to 1.33 V in AZO-based devices. Therefore, Al... 3+ The effect of doping on the surface energy levels of the ZnO electron transport layer: this chemical modulation simultaneously reduces the density of interface trap states and drives the conduction band bottom of AZO to shift upward.

[0071] The charge extraction behavior of the CsPbI2Br perovskite film deposited on the ITO / SnO2 / ZnO substrate prepared in Comparative Example 1 and the CsPbI2Br perovskite film deposited on the ITO / SnO2 / AZO substrate prepared in Example 1 can be characterized by measuring photoluminescence (PL) and time-resolved photoluminescence (TRPL).

[0072] like Figure 4 As shown in a–b, the CsPbI2Br film on SnO2 / ZnO ETL (Comparative Example 1) exhibits a non-uniform PL intensity distribution, while the film on SnO2 / AZO (Example 1) shows a uniform PL imaging with significantly lower emission intensity.

[0073] Figure 4c–d show the corresponding TRPL imaging patterns. Compared with the CsPbI₂Br film prepared in Comparative Example 1, the CsPbI₂Br film prepared in Example 1 exhibits a shorter carrier lifetime and smaller spatial differences on the film surface. This indicates that SnO₂ / AZO ETL can achieve more uniform and efficient charge extraction.

[0074] To further investigate the effect of charge extraction on carrier recombination dynamics, this invention also measures the excitation intensity-dependent TRPL ( Figure 4 e–f). The laser power was gradually increased from 1 μW to 40 μW (a 40-fold increase), and the decay curve was fitted with a double exponential function to extract the carrier lifetime parameters (Tables 2 and 3).

[0075] Table 2. Carrier lifetime parameters of the CsPbI2Br perovskite thin films deposited on ITO / SnO2 / AZO substrates prepared in Example 1. Table 3. Carrier lifetime parameters of CsPbI2Br perovskite films deposited on ITO / SnO2 / ZnO substrates prepared in Comparative Example 1 The average lifetime (τave) obtained by fitting is as follows Figure 4 As shown in e–f, the two samples exhibit distinctly different trends. For the control device, τave increases from 3.00 ns at 1 μW to 5.48 ns at 3 μW, then gradually decreases with further increases in laser power, dropping to 2.05 ns at 40 μW. The initial increase in lifetime can be attributed to trap filling: as the excitation intensity increases, more photogenerated carriers occupy and saturate the existing defect states, thereby suppressing trap-assisted recombination and extending the lifetime. However, beyond the saturation point, the lifetime decreases with further increases in excitation intensity. This is a result of higher-order recombination processes such as Auger recombination and bimolecular recombination gradually becoming dominant at high carrier densities. For the target device, τave decreases slightly from 1.91 ns at 1 μW to 1.44 ns at 3 μW, and then remains essentially constant at approximately 1.35 ns with increasing laser power. The τave value of the target sample is consistently lower than that of the control sample throughout the power range, indicating that the AZO intermediate layer prepared in Example 1 can achieve efficient and uniform electron extraction with negligible interface trap state density. Figure 4 g shows the steady-state photoluminescence (PL) spectra of the perovskite films on the SnO2 / ZnO substrates prepared in Comparative Example 1 and SnO2 / AZO substrates prepared in Example 1, with the emission peak located at approximately 643 nm. The PL intensity of the SnO2 / AZO-based film prepared in Example 1 is lower than that of the SnO2 / ZnO-based film prepared in Comparative Example 1. Figure 4h presents the transient photocurrent (TPC) decay curves, fitted using a double exponential function (Table 4).

[0076] Table 4 The shorter carrier lifetime of the SnO2 / AZO-based device prepared in Example 1, extracted from TPC decay, further confirms its faster charge extraction kinetics. The combination of PL and TPC measurements demonstrates that the SnO2 / AZO ETL prepared in Example 1 possesses efficient and reliable charge extraction capabilities.

[0077] The photoelectric properties of the AZO electron transport layer prepared in Example 1 can be tested using conventional nip solar cells with glass / ITO / SnO2 / ZnO or AZO / CsPbI2Br / PTAA / MoO3 / Ag structures.

[0078] like Figure 5 As shown in Figure a, the device with the AZO intermediate layer prepared in Example 1 achieved a champion power conversion efficiency (PCE) of 16.52%, an open-circuit voltage (VOC) of 1.33V, and a short-circuit current density (JSC) of 16.30mA•cm. -2 These values ​​are comparable to those of ZnO-based devices (PCE is 15.21%, VOC is 1.30V, JSC is 15.64mA•cm). -2 There has been a significant improvement.

[0079] Figure 6 J-V curves for devices with different Al doping concentrations are shown. At 1 at% and 3 at% doping levels, PCE, VOC, JSC, and fill factor (FF) are all effectively improved, with VOC reaching a maximum of 1.35 V. The improvement in FF can be attributed to the charge extraction facilitated by n-type doped AZO under low electric fields.

[0080] Figure 5 b shows the EQE spectra and integrated current densities of the ZnO-based perovskite solar cell prepared in Comparative Example 1 and the AZO-based perovskite solar cell prepared in Example 1. The AZO-based device prepared in Example 1 exhibits significantly enhanced spectral response across the entire measurement range, and its integrated current density ( ) reached 15.37 mA•cm -2 The deviation from the JSC value obtained by J–V measurement is only 5.71%.

[0081] like Figure 5As shown in Figure c, the stable power output of the ZnO-based device prepared in Comparative Example 1 and the AZO-based device prepared in Example 1 are 14.17% and 16.04%, respectively. The corresponding stable current densities at the maximum power point (MPP) are 13.24 and 14.72 mA·cm⁻¹, respectively. -2 The MPP voltages were 1.07 V and 1.09 V, respectively. These steady-state values ​​agree well with the J-V measurements.

[0082] To gain a deeper understanding of charge transport behavior, measurements can be taken at 20 to 100 mW·cm⁻¹. -2 The dependence of VOC on light intensity within the range of measurement ( Figure 5 d). Linear fitting shows that the slope of the AZO-based device prepared in Example 1 is smaller, at 1.46k. B T / q indicates that efficient charge transport effectively suppresses nonradiative recombination and reduces trap density.

[0083] like Figure 5 As shown in Figure e, the dark current density of the AZO device prepared in Example 1 is more than an order of magnitude lower than that of the ZnO device. These results indicate that reducing bulk charge recombination and accelerating interfacial carrier extraction are key factors in improving device performance.

[0084] Figure 5 f presents the forward-reverse scan J-V curves of the AZO-based device prepared in Example 1. Based on these curves, the hysteresis index (HI) can be calculated to be 1.76%, which is lower than the 2.50% of the ZnO-based device (see the corresponding forward-reverse scan for the ZnO device). Figure 7 ).

[0085] Figure 8 Figure a shows the PCE statistical distribution of ETL devices based on ZnO prepared in Comparative Example 1 and AZO prepared in Example 1. Box plots are drawn from data of 25 independent devices under each condition. Compared with ZnO-based devices, AZO-based devices not only exhibit better repeatability but also superior absolute performance values.

[0086] Figure 8 b shows the UV-Vis absorption spectra of the glass / ITO / SnO2 / ZnO or AZO / CsPbI2Br films prepared in Example 1. The absorption edges of both samples are located at approximately 650 nm, with a slight increase in absorption intensity in the AZO-based film. Electrochemical impedance spectroscopy (EIS) was performed to investigate the differences in carrier transport and recombination kinetics.

[0087] Figure 8 c shows the Nyquist plot and the corresponding equivalent circuit model. The series resistance (R0) is obtained from the Nyquist plot by fitting the EIS data using ZView software.S ) and composite resistor (R rec The extracted values ​​are summarized in Table 5. The AZO-based device prepared in Example 1 exhibits a lower series resistance (R0). S ) and higher composite resistance (R rec ).

[0088] Table 5 The electron trap density (N) in the perovskite thin film prepared in Example 1 was estimated using space charge confinement current (SCLC) measurements. trap The single-electron device structure used is ITO / SnO2 / ZnO or AZO / CsPbI2Br / C60 / BCP / Ag, such as Figure 8 As shown in d. The trap density is given by the formula N trap = 2 ε 0 εV TFL / eL 2 Calculate, where ε0 and ε are the vacuum permittivity and the relative permittivity of CsPbI2Br, respectively, and V TFL The trap filling threshold voltage is given, where L is the film thickness and e is the elementary charge. The extracted N... trap The values ​​are as follows: AZO-based devices 1.2 × 10 15 cm -3 ZnO-based devices 1.4 × 10 15 cm -3 The lower trap density of the AZO-based device prepared in Example 1 indicates that the trapped states are suppressed, which facilitates more efficient electron extraction and suppresses nonradiative recombination at the interface, thereby contributing to improved device performance. Thermal conductance spectroscopy was used to evaluate the change in trap state density (tDOS) with energy. Figure 8 e). The AZO-based devices prepared in Example 1 exhibited lower tDOS across the entire energy range, further confirming the important role of efficient electron extraction in reducing bulk defects in perovskite thin films. Finally, to evaluate the electron transport capability of ETL, the J-V characteristics of the glass / ITO / SnO2 / ZnO or AZO / C60 / Ag single-electron devices prepared in Example 1 were measured. Figure 8 f). C60 was introduced to facilitate electron injection from the Ag electrode into the ETL. The AZO-based device prepared in Example 1 exhibited a higher current density than the ZnO-based device. Figure 8 f indicates that Al 3+ Doping effectively enhances the electron transport capability of ZnO, which is beneficial for the transport and extraction of electrons in the perovskite layer.

[0089] The device fabricated in Example 1 achieved a PCE of 16.52%, which is the highest known value for an all-inorganic CsPbI2Br perovskite solar cell with no doping or passivation treatment of the perovskite layer, while also having a high VOC of 1.33V.

[0090] To reveal the operational stability of the unpackaged device, the evolution of the PCE of the device prepared in Example 1 was monitored under a nitrogen atmosphere and continuous standard AM1.5G illumination, with the cell temperature maintained at approximately 50°C during the test.

[0091] like Figure 9 As shown, the AZO-based device prepared in Example 1 maintained 80% of its initial PCE after 662 hours of continuous operation, while the ZnO-based device prepared in Comparative Example 1 decayed to the same level in only 312 hours. This significant improvement in stability highlights the beneficial role of efficient charge extraction in mitigating performance degradation under long-term illumination.

[0092] Figure 10 Top-view and cross-sectional SEM images of the complete device prepared in Example 1 after 700 hours of continuous AM1.5G illumination in a nitrogen atmosphere are shown. In Comparative Example 1, the Ag electrode of the ZnO-based device exhibits significant degradation, with severely fragmented surface morphology and visible voids at the interface between the Ag electrode and the perovskite layer. This degradation is consistent with the Ag electrode corrosion mechanism, namely, the reaction of Ag with iodide ions from the perovskite to form AgI, accompanied by severe morphological changes at the perovskite / electrode interface. Compared to the degradation of the perovskite layer itself, the irreversible degradation of the Ag electrode plays a more critical role in limiting device stability. This demonstrates the crucial role of efficient charge transport in maintaining the long-term operational stability of the device.

Claims

1. A perovskite solar cell, characterized in that: Includes a transparent electrode, the surface of which is loaded with a SnO2 thin film; The surface of the SnO2 film is loaded with an aluminum-doped zinc oxide film; The surface of the aluminum-doped zinc oxide film is loaded with a CsPbI2Br film. The surface of the CsPbI2Br thin film is loaded with a composite hole transport layer. The surface of the composite hole transport layer is loaded with metal electrodes.

2. The perovskite solar cell as described in claim 1, characterized in that: The transparent electrode comprises ITO glass; The aluminum doping content in the aluminum-doped zinc oxide film is 1-5 at%; The composite hole transport layer comprises a PTAA film and a MoO3 film; The metal electrode may be gold or silver.

3. The method for preparing a perovskite solar cell as described in claim 1, characterized in that: Includes the following steps: SnO2 colloidal solution was first spin-coated onto the surface of a transparent electrode and then subjected to a first annealing to load a SnO2 thin film on the surface of the transparent electrode. A ZnO colloidal solution containing aluminum ions is spin-coated onto the surface of a SnO2 film and then subjected to a second annealing to load an aluminum-doped zinc oxide film onto the surface of the SnO2 film. A CsPbI2Br precursor solution was spin-coated onto the surface of an aluminum-doped zinc oxide film for the third time, followed by a third annealing, in order to load a CsPbI2Br film onto the surface of the aluminum-doped zinc oxide film. A composite hole transport layer is loaded onto the surface of a CsPbI2Br thin film; By loading a metal electrode onto the surface of the composite hole transport layer, it is obtained.

4. The method for preparing a perovskite solar cell as described in claim 3, characterized in that: It also includes a step of hydrophilizing the transparent electrode; The hydrophilization includes the step of treating the transparent electrode with ultraviolet light in an ozone atmosphere; The ultraviolet treatment time is 16 minutes.

5. The method for preparing a perovskite solar cell as described in claim 3, characterized in that: The method for preparing the SnO2 colloidal solution includes the step of diluting a raw SnO2 solution with a concentration of 11-13 wt% with water at a volume ratio of 1:3.5-4.5; The first annealing temperature is 140-160℃, and the time is 25-35 min; The first spin coating speed is 4500-5500 rpm.

6. The method for preparing a perovskite solar cell as described in claim 3, characterized in that: The method for preparing the ZnO colloidal solution containing aluminum ions includes the following steps: Zinc salt was dissolved in alcohol, then monoethanolamine was added, and the solution was diluted with alcohol to obtain a ZnO colloidal solution; aluminum nitrate nonahydrate was added to the ZnO colloidal solution. The zinc salt includes zinc acetate dihydrate; The weight-to-volume ratio of zinc acetate dihydrate to alcohol is 16-18 g: 100 mL; The volume ratio of the alcohol to monoethanolamine is 100:7-8; The alcohol includes ethanol; The solid content of the ZnO colloidal solution is 2-3 wt%. The amount of aluminum nitrate nonahydrate added is 0.09-0.48 g of aluminum nitrate nonahydrate per 100 mL of ZnO colloidal solution; The second annealing temperature is 140-160℃, and the time is 25-35 min; The second spin coating speed is 4500-5500 rpm.

7. The method for preparing a perovskite solar cell as described in claim 3, characterized in that: The preparation method of the CsPbI2Br precursor solution includes dissolving CsI, PbI2 and PbBr2 in dimethyl sulfoxide in a molar ratio of 2:1:1 and stirring at 65°C for 3 hours. The concentration of the CsPbI2Br precursor solution was 1 mol / L; The third spin coating includes the following steps: First spin-coat at 1000 rpm for 10 seconds, then spin-coat at 3000 rpm for 40 seconds, and then heat-treat at 100°C within 15 seconds before the end of the third spin-coating. The third annealing includes the following steps: Anneal at 50°C for 30 seconds, then anneal at 200°C for 10 minutes.

8. The method for preparing a perovskite solar cell as described in claim 3, characterized in that: The method for preparing the composite hole transport layer includes the following steps: A 10 mg / mL PTAA chlorobenzene solution was spin-coated onto the surface of a CsPbI2Br film at 4000 rpm for 30 s, followed by annealing at 100 °C for 15 min to obtain a PTAA film. A 6 nm thick MoO3 film was loaded onto the surface of a PTAA film using a thermal evaporation method under vacuum.

9. The method for preparing a perovskite solar cell as described in claim 3, characterized in that: The method for preparing the metal electrode includes the following steps: A 100 nm thick Ag or Au film was loaded onto the surface of a MoO3 film under vacuum using a thermal evaporation method.

10. The application of the perovskite solar cell as described in claim 1, characterized in that: It is used in power generation.